2011
DOI: 10.3233/ch-2011-1386
|View full text |Cite
|
Sign up to set email alerts
|

High-dose atorvastatin treatment in patients with peripheral arterial disease: Effects on platelet aggregation, blood rheology and plasma homocysteine

Abstract: Background: Statins are used for the treatment of hypercholesterolemia. Although they are well known to have pleiotropic effects, their dose-dependent influence on platelet aggregation, hemorheologic properties and the plasma levels of homocysteine in patients with peripheral arterial disease (PAD) has not been thoroughly investigated so far.Methods and results: From a total of 100 patients with PAD 48 patients were randomized to a treatment with atorvastatin 80 mg/d for six months, and 52 patients served as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Consistently, metaregression analyses suggested a marginally significant positive dose-response trend between the percent use of lipid-lowering drugs and log-RR, and a marginally significant inverse dose-response trend between percent baseline hypertension and log-RR for total cancer incidence risk associated with folic acid supplementation. A recent study 32 reported an increase in homocysteine levels in the presence of rather elevated levels of folic acid after high-dose atorvastatin treatment, which suggests that statins treatment may play an important role in the homocysteine metabolic cycle and may possibly affect cancer risk associated with folic acid supplementation. Higher total folate intake was associated with a decreased risk of incident hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Consistently, metaregression analyses suggested a marginally significant positive dose-response trend between the percent use of lipid-lowering drugs and log-RR, and a marginally significant inverse dose-response trend between percent baseline hypertension and log-RR for total cancer incidence risk associated with folic acid supplementation. A recent study 32 reported an increase in homocysteine levels in the presence of rather elevated levels of folic acid after high-dose atorvastatin treatment, which suggests that statins treatment may play an important role in the homocysteine metabolic cycle and may possibly affect cancer risk associated with folic acid supplementation. Higher total folate intake was associated with a decreased risk of incident hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Also, in another study carried out by Navarro et al, serum Hcy levels did not alter significantly in diabetic patients on hemodialysis, despite improvement in lipid profile and hsCRP levels by atorvastatin administration (31). However, Van der Loo et al, revealed that administration of 80 mg/d of atorvastatin led to an increase in Hcy plasma levels in patients with peripheral arterial disease (33). The contradictories in different studies can be partly due to the dose of statins, the intervention duration, different types of diseases and patients' metabolic profiles.…”
Section: Discussionmentioning
confidence: 91%
“…Of note, Van der Loo et al showed that treatment with 80 mg atorvastatin resulted in an increase of homocysteine plasma levels in the presence of rather elevated levels of folic acid among patients with peripheral arterial disease ( 24 ).…”
Section: Discussionmentioning
confidence: 99%